46.8k views
0 votes
Solve using quadratic formula:3k^2 - k - 7 = 0

User Skyhan
by
4.9k points

1 Answer

1 vote

Answer:

The solution to the given quadratic equation is:

k = 17.03, -1.37

Step-by-step explanation:

Given the equation:


3k^2-k-7=0

Solving this using the quadratic formula, we have:


\begin{gathered} k=\frac{-(-1)\pm\sqrt[]{(-1)^2-4(3)(-7)}_{}}{2(3)} \\ \\ =\frac{1\pm\sqrt[]{1+84}}{6} \\ \\ =\frac{1\pm\sqrt[]{85}}{6} \end{gathered}

Therefore,


\begin{gathered} k=\frac{1+\sqrt[]{85}}{6} \\ \\ =17.03 \end{gathered}

OR


\begin{gathered} k=\frac{1-\sqrt[]{85}}{6} \\ \\ =-1.37 \end{gathered}

User Khanh Nguyen
by
4.7k points